2011
DOI: 10.2754/avb201180020131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic and organic zinc supplementation on coccidial infections in goat kids

Abstract: The aim of this study was to identify the effect of zinc-enriched diet fed to goats and their kids on the number of Coccidia oocysts shed by kids, on clinical signs of coccidiosis, weight gains, and kids' blood plasma concentration of zinc. A total of 22 goat kids were divided into 4 groups of 5 or 6 animals. Goats and kids from the control group did not receive any additional zinc, the second group was supplemented with inorganic zinc (zinc oxide), the third group was given zinc lactate, and the fourth group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These findings are in agreement with previous reports in different animal species, in sheep (Senosy et al, 2018;Abdelrahman et al, 2017 andJalilian et al, 2012), in goats (Pechova et al, 2009), in kids goats (Strnadová et al, 2011;Palenikova et al, 2014), in dairy cows (Kinal et al, 2007). Increasing of serum concentration of phosphorus and copper are due to supplementation of microelements with the bioavailability of microorganisms in rumen led to better transfer of trace elements to the tissues, including blood (Spears, 1996;Olson et al, 1999;Huert et al, 2002).…”
Section: Changes In Serum Mineral Concentrations During Pregnancy Stagessupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in agreement with previous reports in different animal species, in sheep (Senosy et al, 2018;Abdelrahman et al, 2017 andJalilian et al, 2012), in goats (Pechova et al, 2009), in kids goats (Strnadová et al, 2011;Palenikova et al, 2014), in dairy cows (Kinal et al, 2007). Increasing of serum concentration of phosphorus and copper are due to supplementation of microelements with the bioavailability of microorganisms in rumen led to better transfer of trace elements to the tissues, including blood (Spears, 1996;Olson et al, 1999;Huert et al, 2002).…”
Section: Changes In Serum Mineral Concentrations During Pregnancy Stagessupporting
confidence: 91%
“…Average body weight of kids born to goat dams fed (30 mg Cu/ kg DM) inorganic or organic forms were higher (Palenikova et al, 2014;Solaiman et al, 2007). Moreover, kids supplemented (60 mg Zn/ kg DM) organic or inorganic forms with diets showed significantly higher average daily gain compared with control (Strnadová et al, 2011). While growth performance of (Dorper × Mongolia) lambs fed (10 or 20 mg Cu/kg DM) to the basal diet did not differ (Cheng et al, 2008).…”
Section: Productive Traits Of Newly Born Lambsmentioning
confidence: 99%
See 1 more Smart Citation
“…In broilers, Bun et al (2011) reported no effects of dietary organic Zn levels on ADG or DMI. However, effects of organic and inorganic Zn sources on Eimeria infections in goat kids have shown reduced oocyst shedding in unsupplemented and Zn oxide supplemented kids compared with Zn chelate and Zn lactate supplemented kids ( Strnadová et al, 2011 ). Of 156 tested fecal samples in the present study, only 4.5% had total fecal oocyst counts less than 100 oocyst per gram (opg) and 11.5% of samples contained more than 10,000 opg, suggesting that coccidiosis spreads easily in an infected population of lambs and can pose a persistent problem.…”
Section: Discussionmentioning
confidence: 99%